Reflecting rehabilitation nursing care: Theory of Recognition crossed by the Principle of Hope - Milena Amorim Zuchetto; Soraia Dornelles Schoeller; Caroline Porcelis Vargas; Lucas Antunes; Mara Ambrosina de Oliveira Vargas (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective The study seeks to reflect on rehabilitation nursing care, from the perspective of the Theory of Recognition and the Principle of Hope. State of art Reflection study, based on Axel Honneth's Theory of Recognition crossed by Ernst Bloch's Principle of Hope, aiming to elucidate the theoretical and methodological potential of these references for future research in health, nursing and rehabilitation nursing. Rehabilitation nursing care is permeated by theoretical and philosophical influences little described in the literature. The study proposes a way of thinking and exercising care with the perspective of building rehabilitation nursing care, in which the nurse excels in trust, respect and mutual esteem, playing the role of agent of hopeful and realistic expectations. Conclusion The study showed the main characteristics of each philosophical theoretical axis, permeating, separately, the relevant definitions to understand its implications in the concrete reality of living.